Single-Cell Quantification of a Highly Biocompatible Dinuclear Iridium(III) Complex for Photocatalytic Cancer Therapy - Fan Z.; Rong Y.; Sadhukhan T.; Liang S.; Li W.; Yuan Z.; Zhu Z.; Guo S.; Ji S.; Wang J.; Kushwaha R.; Banerjee S.; Raghavachari K.; Huang H. (My University, 2025)
Quantifying the content of metal-based anticancer drugs within single cancer cells remains a challenge. Here, we used single-cell inductively coupled plasma mass spectrometry to study the uptake and retention of mononuclear (Ir1) and dinuclear (Ir2) IrIII photoredox catalysts. This method allowed rapid and precise quantification of the drug in individual cancer cells. Importantly, Ir2 showed a significant synergism but not an additive effect for NAD(P)H photocatalytic oxidation. The lysosome-targeting Ir2 showed low dark toxicity in vitro and in vivo. Ir2 exhibited high photocatalytic therapeutic efficiency at 525 nm with an excellent photo-index in vitro and in tumor-bearing mice model. Interestingly, the photocatalytic anticancer profile of the dinuclear Ir2 was much better than the mononuclear Ir1, indicating for the first time that dinuclear metal-based photocatalysts can be applied for photocatalytic anticancer treatment. © 2022 Wiley-VCH GmbH.